Assessing Oil and Non-Oil GDP Growth from Space : An Application to Yemen 2012-17 - Debbich, Majdi (Washington, D.C. : International Monetary Fund, 2019)
This paper uses an untapped source of satellite-recorded nightlights and gas flaring data to characterize the contraction of economic activity in Yemen throughout the ongoing conflict that erupted in 2015. Using estimated nightlights elasticities on a sample of 72 countries for real GDP and 28 countries for oil GDP over 6 years, I derive oil and non-oil GDP growth for Yemen. I show that real GDP contracted by a cumulative 24 percent over 2015-17 against 50 percent according to official figures. I also find that the impact of the conflict has been geographically uneven with economic activity contracting more in some governorates than in others.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet